Teaching modules for estimating climate change impacts in economics courses using computational guided inquiry. Issue 2 (2nd April 2020) - Fortmann, Lea; Beaudoin, Justin; Rajbhandari, Isha; Wright, Aedin; Neshyba, Steven; Rowe, Penny
Abstract: The authors of this article introduce two teaching modules that aim to increase climate literacy and active learning in undergraduate economics courses through the incorporation of real-world data and modeling. These modules are based on the concept of computational guided inquiry (CGI), which combines a guided inquiry approach within a computational framework, such as Excel. In one module, students estimate and graph expected marginal damages due to regional sea level rise for various polar ice melt scenarios. In the second module, students partially replicate a journal article estimating the total economic value of ecosystem services in the Arctic. These modules have been used in urban, environmental, and climate change economics courses, and are ready to be implemented with minimal upfront cost to instructors.